Analysis of Geosynthetic – Reinforced Stone Piles – Supported Embankments - RamazanBorujerdi, Ali (Journal of Sustainable Underground Exploration, 2023)
The low bearing capacity, high compressibility, and lack of lateral resistance of stone pile-supported embankments on soft clay deposits pose design challenges. To overcome these difficulties, geosynthetics have been widely favored by geotechnical engineers in recent years. A two and three dimensional (2D, 3D) finite element model study that simulates a geosynthetic-reinforced and geosynthetic-encased stone pile-supported embankment on soft ground is presented in this paper. To study the effect of reinforcement and encasing on the vertical displacement of stone piles and soft soil, numerical analyses are performed. The results show a significant reduction in settlement with the casing, which is believed to be a direct result of the additional containment pressure created by the geosynthetic casing. With the help of soil reinforcement, the surface settlement values ??of the soft soil could be significantly reduced.